Synergistic Effects of Content Structure and Sensory Elements: Exploring the Impact Mechanism of Tourism Short Videos on Travel Intention - Wang , Meng; Xie, Xiaofang; Zhang, Hejie; Du, Yue; Chu, Zhe (Transformations In Business & Economics, 2025)
Tourism short videos have become pivotal tools that influence tourists’ decision-making amid the rapid development of digital marketing. Existing studies inadequately address the mechanisms through which short video content shapes travel intentions. To explore the relationship between content structure and sensory elements, the interaction mechanisms between content structure and sensory elements in tourism short videos and their impacts on travel intention were unravelled by employing narrative communication theory and information processing fluency theory through two scenario-based experiments. The synergistic effects of video content structures (narrative vs. non-narrative) and sensory elements (visual–content matching, background music tempo) in consumer decision-making processes were examined. Results reveal that narrative short videos significantly enhance travel intentions by evoking emotional resonance through plot development and character portrayal. The visual–content matching effect plays a critical role. Slow-tempo compositions intensify emotional immersion in narrative videos, while fast-tempo tracks amplify visual salience and instantaneous attentional capture in non-narrative formats. These conclusions elucidate the interaction mechanisms underlying content–sensory synergy in tourism short videos, thus providing theoretical foundations for video dissemination strategies and practical guidance for content creation in destination marketing.